Irregular response of nanofluid flow subject to chemical reaction and shape parameter in the presence of variable stream conditions - R. Kandasamy; Hatem Sabeeh Altaie; Izzatun Nazurah Binti Zaimuddin (Alexandria Engineering Journal, 2016)
The problem of boundary layer of nanofluid flow which results from the stretching of a flat surface has been investigated numerically. The model includes the effects of Brownian motion, magnetic effect, non-linear velocity, variable thickness, thermophoresis, chemical reaction, porous medium, shape, thickness and heat source. The Partial differential equations are converted to ordinary deferential equations to solve analytically using shooting technique. The velocity, temperature and concentration profiles are discussed in detail for all parameters.